2020
DOI: 10.4314/ijbcs.v14i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Diversité floristique et structure démographique des peuplements ligneux des parcours naturels sahéliens du Sud-Est du Niger : Cas de l’enclave pastorale « Dadaria » (Mainé-Soroa, Diffa)

Abstract: L’enclave pastorale de Dadaria située dans le département de Mainé-Soroa est devenue une zone de concentration d’animaux locaux et transhumants durant toute l’année. La présente étude vise à caractériser la diversité floristique et la structure démographique des groupements ligneux cette enclave. Les données floristiques et dendrométriques ont été collectées dans 53 placettes de 2500 m² et la régénération a été appréciée dans des placeaux de 25 m². Les résultats montrent une flore ligneuse très pauvre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
2
0
0
6
Order By: Relevance
“…For the woody plants, they are Afzelia africana, Pterocarpus erinaceus, Khaya senegalensis, Ficus gnaphalocarpa, Securinega virosa, Baissea multiflora. These results are related to that obtained by Idrissa et al (2020) in the pastoral enclave of Dadaria, Diffa region in Niger, and by Kiema et al (2014) in Burkinabe faso, who indicated that the area of vegetation cover is declining, reflecting a decline in certain species. Degradation of pastures resulting in a decrease in the availability of fodder biomass, a decrease in the diversity of fodder species, with well-favored species such as Andropogon gayanus Kunth, Brachiaria lata (Schumach.)…”
Section: Adverse Effects Of Climatic Hazards On Pastoral Resources De...supporting
confidence: 84%
“…For the woody plants, they are Afzelia africana, Pterocarpus erinaceus, Khaya senegalensis, Ficus gnaphalocarpa, Securinega virosa, Baissea multiflora. These results are related to that obtained by Idrissa et al (2020) in the pastoral enclave of Dadaria, Diffa region in Niger, and by Kiema et al (2014) in Burkinabe faso, who indicated that the area of vegetation cover is declining, reflecting a decline in certain species. Degradation of pastures resulting in a decrease in the availability of fodder biomass, a decrease in the diversity of fodder species, with well-favored species such as Andropogon gayanus Kunth, Brachiaria lata (Schumach.)…”
Section: Adverse Effects Of Climatic Hazards On Pastoral Resources De...supporting
confidence: 84%
“…The high density of small diameter classes ensures the renewal of natural forest ecosystems while low densities of large trees result on natural selection. Similar structures have been shown in the Niokolo-Koba National Park of Senegal (Larrue, 2002) and in protected areas in the southern of Niger (Abdourhamane et al, 2013;Idrissa et al, 2020). Authors found the same profile of forest stands structure in Benin using a diameter threshold of 10 cm (Bonou et al, 2009;Houeto et al, 2013).…”
Section: Structure Of the Woody Vegetationsupporting
confidence: 69%
“…La richesse floristique des sites étudiés est légèrement inférieure à celle obtenue par les travaux effectués au Tchad qui comptent 18 espèces, 15 genres et 9 familles (Mahamat Saleh et al, 2015b). Elle est légèrement élevée par rapport à celle du Guera au Tchad avec 11 espèces, 7 familles (Ngarnougber et al, 2017), des zones sahéliennes du Niger avec 10 espèces, 7 familles et 8 genres (Idrissa et al, 2020) et du Sénégal avec 12 espèces, 10 genres et 7 familles (Diallo et al, 2011). Cependant, elle est pratiquement identique à celle rencontrée au Niger qui présente 15 espèces, 11 genres et 10 familles (Ousseina et al, 2015).…”
Section: Discussionunclassified
“…Cette différence serait due aux conditions climatiques extrêmes que connait le milieu ces dernières années d'une part et d'autre part à la pression anthropique et animale. L'effet combiné de ces facteurs fait régresser voire disparaitre de nombreuses espèces ligneuses (Idrissa et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation